2017
DOI: 10.22159/ajpcr.2017.v10i3.16071
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoids, Eugenol Scaffold, and Its Derivatives as Anticancer

Abstract: Eugenol (EU) is a phenylpropene, an allyl chain-substituted guaiacol. EU is a member of the phenylpropanoids class of chemical compounds. It is a colorless to pale yellow oily liquid extracted from certain essential oils especially from clove oil. Further, chemopreventive agents might be used singly or in combination with chemotherapy or radiotherapy for the more effective treatment of cancer by enhancing the efficacy of these modalities with minimal side effects and toxicity. Considering that EU scaffold may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Eugenol has shown potential anticancer activity against colon, gastric, breast, prostate, and skin cancer, as well as melanoma and leukemia [23]. Eugenol inhibits tumor proliferation and formation, increases reactive oxygen species (ROS), generates apoptosis, and has a genotoxic effect in different cancer cells [23,[29][30][31]. El-Saber Batiha, G. et al [4] collected information related to Eugenol Pharmacokinetic and Toxicity Studies.…”
Section: Eugenolmentioning
confidence: 99%
“…Eugenol has shown potential anticancer activity against colon, gastric, breast, prostate, and skin cancer, as well as melanoma and leukemia [23]. Eugenol inhibits tumor proliferation and formation, increases reactive oxygen species (ROS), generates apoptosis, and has a genotoxic effect in different cancer cells [23,[29][30][31]. El-Saber Batiha, G. et al [4] collected information related to Eugenol Pharmacokinetic and Toxicity Studies.…”
Section: Eugenolmentioning
confidence: 99%
“…Cloves may also help your liver work better. Some studies have shown that eugenol found in cloves can also help reduce signs of liver cirrhosis and fatty liver disease [66][67][68].…”
Section: Nutrients Per Servingmentioning
confidence: 99%
“…Eugenol has shown potential anticancer activity against colon, gastric, breast, prostate, melanoma, leukemia, or skin cancer [14]. Eugenol inhibits tumor proliferation and formation, increases the reactive oxygen species (ROS), generates apoptosis, and has a genotoxic effect in different cancer cells [14,[20][21][22].…”
Section: Ceo Compositionmentioning
confidence: 99%